RETRACTED: Improvement of methods for obtaining phosphorus fertilizers by mechanical activation - Olzhaev Dilshod; Akhmedova Nazira (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001